Pelatihan menulis berita di website kepada mahasiswa Program Studi Perpustakaan dan Sains Informasi Universitas Islam Negeri Salatiga - Suryanto, Suryanto; Syaputri, Diana; Mahmudah, Siti (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
News quality is one factor affecting the readability of news on a website. PdSI study program students who are among the news writers on the study program website need to improve their writing skills, so students need to take part in news writing training. This service aims to provide students of the Library and Information Science Program (Prodi PdSI) with training on writing news articles for a website. The service employs the Service Learning (SL) method, which consists of three stages: Pre-Implementation, Implementation, and Post-Implementation. During the training phase, the facilitators collaborated with a third party, Skill Academy. The training was titled “Jurnalistik: Teknik Menulis Naskah Berita Seperti Jurnalis Andal” by Prita Kusuma. The training materials included a pre-exam, 12 learning modules, and a post-exam. The training sessions successfully benefited students, as they became knowledgeable and skilled in writing news articles for websites. In addition to benefiting the students, this training also positively impacted the study program, as it now has students capable and competent in writing news articles about activities related to the program.